Orquideoflórula de un sector de Serranía de La Cuchilla, municipio Caripe, estado Monagas, Venezuela - Leopardi, Carlos (2013)
To contribute with the study of the Orchidaceae on El Macizo Montañoso del Turimiquire, field exploration was done in a sector of the Serranía de La Cuchilla, Caripe municipality, Monagas state (10°07,00’N 63°33,45’O), during the years 2005-2008, in the months of Decembe-January, May and July- September. Collected specimens were housed in the Herbarium IRBR with duplicates at VEN. As result, 47 species in 30 genera were identified. The most importantr genera are Epidendrum (8 spp.), Pleurothallis s.l. (3 spp.) and Prosthechea (3 spp.); the most frequent species are: Epidendrum subpurum, Acianthera lanceana and Scaphyglottis fusiformis. Additionally, a new record to the east portion of Cordillera de la Costa is reported: Acianthera miqueliana. Finally, 20% of species are mentioned in the Red Book of Venezuelan Flora: one in critic danger (Cattleya gaskelliana), three as vulnerable, one in danger, three as minor risk, and one (Prosthechea venezuelana) as insufficiently known. An identification key to the species and pictures of some of the taxa are presented.